The Political Philosophy of Shibli Nomani: A Critical Study - Razia Sultana (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
This paper discusses the political thought of Allama Shibli Nomani, a distinguished scholar, historian, and reformer of colonial India, whose ideas reflect a deep concern for the socio-political decline of Muslims under British rule. Shibli envisioned the revival of the Muslim community through intellectual awakening, moral reform, and modern education rooted in Islamic values. His political philosophy combined faith and rationalism, drawing inspiration from the early Islamic model of governance while engaging critically with Western political ideologies. The paper discusses his emphasis on unity among Muslims, the importance of self-reliance, and his advocacy for educational institutions that could produce morally upright and politically conscious individuals. It also explores Shibli’s efforts to redefine the relationship between religion and politics, highlighting his belief that Islam provides a comprehensive system guiding all aspects of life. Through an analytical study of his writings, particularly his historical works and letters, this research seeks to present Shibli Nomani as a visionary thinker whose political ideas contributed significantly to shaping Muslim intellectual and political discourse in modern India.